Control tactics and evaluation of clinical efficacy of therapy in children with bronchial asthma associated with mycoplasma infection - L. G. Gorina; N. А. Krylova; I. V. Rakovskaya; S А. Goncharova; O. I. Barkhatova (Туберкулез и болезни лёгких)
The uncontrolled course of bronchial asthma (BA) in children and insufficient efficacy of standard therapy regimens may be due to underestimated infectious factors. The objective: to study specific parameters of the course and treatment of mycoplasma infection, improve monitoring over BA therapy in children of the tender and preschool age. Subjects and methods. 320 children with BA in the age from 1 to 7 years old were followed up. In this work, Mycoplasma pneumoniae (FH), Mycoplasma hominis (H-34), Ureaplasma urealyticum (serotype 8), Mycoplasma fermentans (PG18) and Mycoplasma arthritidis (PG6) were used, they were cultured on a liquid medium for cultivation of mycoplasmas and ureaplasmas. To isolate CIC from blood serum samples, we used the method of precipitation with 3.5% polyethylene glycol (PEG, 6000 Da), hemagglutination assays and IFA were used to identify mycoplasma antigens, mycoplasma DNA was detected by PCR with InterLabService diagnostic kits. The data of 47 patients with prolonged mycoplasma antigenemia were assessed at the baseline and in 1.5-3 months after the treatment course of azithromycin.Results. 320 blood serum samples from children with BA were tested, and the detection rate by hemagglutination assays of M. pneumoniae antigens was 60.9%, M. hominis – 43.4%, U. urealyticum – 44.8%, M. arthritidis – 29.7%, M. fermentrans – 45.3%. The assessment of relationship between of M. pneumoniae, M. hominis and asthma exacerbation showed that antigens of M. pneumoniae and M. hominis were found in 216 children (single or associated). After treatment with azithromycin, the frequency of BA exacerbations within 3 months decreased by 2.4 times, as well as there was a reduction in the number of samples positive for antigens and DNA of mycoplasma in a free state and within CIC. The persistence of antigens, DNA of M. pneumoniae and M. hominis before treatment of 47 children was 80.9 and 66.0% of cases, after treatment with azithromycin – 31.9 and 25.5% of cases, respectively (p < 0.001). Within CIC isolated from the blood serum of patients, antigens to M. pneumoniae and M. hominis before treatment were detected by IFA in 63.8 and 70.2% of children, after treatment – in 31.9 and 23.4%, respectively. p < 0.001. In blood samples, DNA of M. pneumoniae and M. hominis was detected by PCR before treatment in 8.5 and 34.0%; after treatment in 6.4% (p = 0.318) and 19.1% of cases, respectively (p = 0.009), and within CIC isolated from blood serum, in 27.7 and 48.9% of cases before treatment and 8.5 and 34.0% after it, respectively (p = 0.009).